Vaccination status and causes of under vaccination in paediatric patients admitted at Khyber teaching hospital Peshawar - Shahab, Faseeh; Hussain, Hamid; Gul, Hamdan (Journal of Postgraduate Medical Institute, 2013)
To assess the vaccination status of the admitted pediatric population in Khyber Teachinghospital Peshawar and to compare the findings in the data collected during June 2006 and February 2010.A hospital based survey was conducted in the pediatric population admitted in the department of PediatricsKTH Peshawar, in June, 2006 and February, 2010. Those children whose parents gave consent forthe collection of data based on a questionnaire were included in the study. Data was collected from parentsof 81 children on both the occasions. We found that 40% of patients had up-to-date vaccinationprofile in 2006 while it was 33% for 2010 (p-value 0.54). Twenty-seven (33.3%) children had no history ofvaccination in 2006, while thirty-seven (45.6%) children were not vaccinated in 2010 (p-value 0.30). In2006 the underlying causes of no vaccination were lack of awareness (74%) and peer pressure (11%) whilein 2010; internal displacement of the patients which precluded vaccination (43%) and lack of awareness(32%) were the main causes. There was no statistical difference between lack of awareness amongst parentsof patients in 2006 and 2010 (p-value 0.08). Awareness for polio and participation in supplementaryvaccination activities for polio was high in 2006 (97%) and in 2010 (87%). A low rate of vaccination wasfound in children during both time-periods. Lack of awareness regarding the standard EPI schedule wasthe main factor in 2006 while internal displacement of the patients was the main underlying cause ofunder-vaccination in 2010.